1975
DOI: 10.1111/j.1432-1033.1975.tb02466.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Studies on Tyrosinase Induction in Neurospora

Abstract: An immunoassay for tyrosinase, using the modified bacteriophage technique, was developed : Tyrosinase of Neurospora was conjugated to bacteriophage T4 using glutaraldehyde as a cross-linking agent. The conjugated phage that survived the coupling process could be inactivated by antiserum raised in rabbits against pure tyrosinase, but not by normal serum. This inactivation was specifically inhibited by pure Neurospora tyrosinase, and the degree of inhibition was proportional to the concentration of tyrosinase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The pure enzyme had an extinction coefficient AXl%cm of 22 at 280 nm [4]. The determination of the specific activity was carried out according to Fling et al [2] and the obtained value, 1100 units per mg protein, is slightly higher than those reported by others [2,3,9].…”
Section: Proteinmentioning
confidence: 71%
“…The pure enzyme had an extinction coefficient AXl%cm of 22 at 280 nm [4]. The determination of the specific activity was carried out according to Fling et al [2] and the obtained value, 1100 units per mg protein, is slightly higher than those reported by others [2,3,9].…”
Section: Proteinmentioning
confidence: 71%
“…Freshly isolated enzyme contained about 30% oxytyrosinase as has been reported by Gutterridge and Robb [5] using a different purification method. The specific activity of the purified enzyme measured by the procedure of Fling et al [4] was slightly higher than the ones reported by Gutteridge and Robb [5], Katan et al [9], and Fling et al [4]. The enzyme was stored in 10 mM sodium phosphate buffer, pH 7.2, + 0.5 M NaC1 at 4°C.…”
Section: Preparation Of Enzymementioning
confidence: 87%
“…Sci. USA 75 (1978) indications (8,22) that methionine is the sole sulfur-containing amino acid in Neurospora tyrosinase, the enzyme was found to contain also a single chemically modified cysteine residue. Digestion of in dvo labeled [asSityrosinase with pepsin resulted, in addition to the three methionine peptides, in a fourth radioactive peptide with the amino acid composition 0.95 Thr, 2.00 Gly, 0.91 Tyr, and an unknown ninhydrin-positive, radioactive species "X" eluting just after aspartic acid.…”
Section: ~~~E Enimentioning
confidence: 99%